Tratamento por osmose inversa de efluentes gerados na produção do soro do leite em pó - Basso, Caroline Diehl (2014)
The study aimed to use reverse osmosis to treat the wastewater generated in the demineralization of whey, seeking to improve the quality so that it is capable of reuse by industry. For this, these waste waters are submitted to a pilot based assays reverse osmosis system which follow an experimental planning 22, using temperatures of 20 °C and 45 °C and pressures of 10 bar and 20 bar as independent variables to obtain the best physico-chemical quality of the permeate. The results show that the operating pressure and temperature have a direct effect on the permeate flux, although they showed no influence on the membrane rejections. The best permeate flow was obtained in the condition of 45 °C and 20 bar, corresponding to 102.11 Lm-2.h-1. This experimental condition showed rejections of 95.89% for turbidity, electrical conductivity for 95.65%, 96.59 % for total solids, 100% for soluble solids, 87.15% for total nitrogen, 90.09% for ammonia nitrogen, 52.29% for oils and greases, 99.09% for chemical oxygen demand, 99.58% to 97.33% for lactose and color, demonstrated that membrane separation process by reverse osmosis enables the after treatment of the effluent generated in the nanofiltration production of whey powder phase, enabling the generation of reuse water, non-potable uses such as cleaning and replacement of external water towers cooling and boiler